Virome-wide serological profiling reveals association of herpesviruses with obesity - Mohammad Rubayet Hasan (8602080) (2021)
The relationship between viral infection and obesity has been known for several decades but epidemiological data is limited to only a few viral pathogens. The association between obesity and a wide range of viruses was assessed using VirScan, a pan-viral serological profiling tool. Serum specimens from 457 Qatari adults (lean = 184; obese = 273) and 231 Qatari children (lean = 111; obese = 120) were analyzed by VirScan. Associations with obesity were determined by odds ratio (OR) and Fisher’s test (p values), and by multivariate regression analysis to adjust for age and gender. Although there was no association of viral infections with obesity in the pediatric population, a nominal association of obesity with seropositivity to members of the Herpesviridae family is observed for the adult population (OR = 1.5–3.3; p < 0.05). After adjusting p values for multiple comparisons (Bonferroni correction) the odds of being obese is significantly higher in herpes simplex virus 1 (HSV-1) seropositive Qatari adults (OR = 3.3; 95% CI 2.15–4.99; p = 2.787E − 08). By VirScan, the sero-prevalence of HSV1 is 81.3% and 57.1% among Qatari obese and lean adult populations, respectively. Higher prevalence of antibodies against several peptide epitopes of HSV-1/2 is positively associated with obesity (OR = 2.35–3.82; p ≤ 3.981E − 05). By multivariate regression analysis, HSV-1 was independently associated with obesity irrespective of age and gender. Our results suggest that obesity among Qataris may be associated with a higher prevalence of herpesvirus infections, in particular HSV-1. Furthermore, the high prevalence of antibodies against peptide antigens specific to HSV-1 and -2 in the obese population suggests that these viral peptides may play a role in adipogenesis. Further studies with these candidate peptides in cell culture or animal models may confirm their adipogenic roles. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-021-82213-4